قراءة قانونية اقتصادية لصيغ استغلال العقارات الوقفية الموجهة للاستثمار على ضوء المرسوم التنفيذي رقم 18 - 213 .: An legal economic reading of the formulas for the exploitation of investment endowment properties in the light of Executive Decree No. 18-213. - عيادة الحسين; عبد القادر قداوي (Journal of North African Economies, 2025)
This study aims to identify the formulas adopted by the Algerian legislator in the exploitation of endowment, real estate directed to the completion of investment projects brought, by Executive Decree No. 18-213, and to read them legally and economically, the latter of which led us to wonder what methods and formulas the legislator adopted in exploiting, endowment properties directed to the completion of investment projects brought by Executive Decree No. 18-213 and the effectiveness of these methods and formulas economically? In order to answer this problem, we decided to divide the research into two axes, since axis 1 dealt with the original formula, for the conclusion of the contract for the exploitation of the Waqf real estate destined, for investment and axis 2 dealt with the exceptional formula for the conclusion of this contract, and by extrapolating the provisions of this decree we concluded that the legislator adopted two formulas: the formula of bidding as a general asset and the exception of the formula of consent in the conclusion of this contract.